Argentina: a decade of the convertibility regime - Frenkel, Roberto (2002)
This article originated as a paper prepared for the conference Economic Management and Political Collapse in Argentina: Interpreting the Past to Build for the Future, organized by the Graduate Program in International Affairs, The New School, New York, April 8-9, 2002